Quantum Communication-Celebrating the Silver Jubilee of Teleportation - Liss, Rotem; Mor, Tal (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
To celebrate the 25th anniversary of the seminal 1993 quantum teleportation paper, we are pleased to present research works, reviews, and stories about quantum communication, quantum entanglement, and quantum teleportation: (1) How was quantum teleportation invented? (2) Which teleportation experiments were performed at the Sapienza University in Rome? (3) Can we use joint measurements to generate nonclassical correlations? (4) How is classical sampling related to quantum entanglement? (5) How is classical communication related to a special quantum ensemble? (6) How can simplifying a quantum key distribution protocol make it insecure? (7) Can we teleport a two-qubit quantum state using a nonsymmetric channel? This book includes submissions by some of the most prominent quantum teleportation contributors, including Gilles Brassard, Francesco De Martini, Nicolas Gisin, and William K. Wootters, as well as additional researchers, all presenting their up-to-date insights regarding quantum communication.